2016
DOI: 10.1016/j.chc.2016.06.005
|View full text |Cite
|
Sign up to set email alerts
|

Technology-based Interventions for Preventing and Treating Substance Use Among Youth

Abstract: Summary Preventing or mitigating substance use among youth generally involves three different intervention frameworks: universal prevention, selective prevention, and treatment. Each of these levels of intervention poses unique therapeutic and implementation challenges. Technology-based interventions provide solutions to many of these problems by delivering evidence-based interventions in a consistent and cost-effective manner. This article summarizes the current state of the science of technology-based interv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
45
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(48 citation statements)
references
References 74 publications
1
45
0
2
Order By: Relevance
“…As the youth answers the questions, the program can record her responses, giving investigators quantified fidelity data. When the program moves to scale, those involved in its implementation can similarly monitor fidelity [1**]. Implementation integrity can be enhanced in computer-based programs when provisions are in place to limit inattention, intentionally skipped content, and overlooked material.…”
Section: The Promise Of Computer-based Programsmentioning
confidence: 99%
See 1 more Smart Citation
“…As the youth answers the questions, the program can record her responses, giving investigators quantified fidelity data. When the program moves to scale, those involved in its implementation can similarly monitor fidelity [1**]. Implementation integrity can be enhanced in computer-based programs when provisions are in place to limit inattention, intentionally skipped content, and overlooked material.…”
Section: The Promise Of Computer-based Programsmentioning
confidence: 99%
“…Unsurprisingly, the delivery of substance use prevention and intervention services efforts for youth is also employing new technologies in the form of computer-based programs. Computer-based programs offer promise to improve prevention and intervention efficacy, cost structure, logistics, responsiveness, and availability [1**]. Still, challenges remain before computer-based prevention and intervention programs realize their potential.…”
Section: Introductionmentioning
confidence: 99%
“…A national survey of high school counselors, however, revealed that school counselors reported low levels of training in substance abuse screening, assessment, and individual interventions and limited training opportunities through their school or school districts (Burrow‐Sanchez & Lopez, 2009). Thus, interventions delivered through technology can improve both access and intervention fidelity while requiring little training and reducing costs associated with program implementation (Lord & Marsch, 2011; Marsch & Borodovsky, 2016).…”
mentioning
confidence: 99%
“…Using such technologies to deliver potentially low-cost, time-saving, high-fidelity SBIRT programs may be a compelling way to increase uptake of SBIRT among health care providers. 13,14 Reviews of these technologies suggest that they can be effective for improving substance use outcomes among patients, are feasible to use, and are acceptable to patients. 13,15 Better patient outcomes may be achieved by combining technology-based programs with in-person provider intervention.…”
mentioning
confidence: 99%